The termination of life (Revista do Tribunal Regional Federal da 3ª Região, 2013)
We propose to examine some problems related to the end of human life. Our analysis is also a legal one. That's why we begin by situating life in the fundamental legal diplomas. These proclaim the defense of life and its intrinsic value. In its Preamble, the Federal Constitution sets out to ensure the values of a fraternal society. Article 1, III, states that the dignity of the human person is the foundation of the Brazilian state. In Article 4, II, it affirms the prevalence of human rights in international relations. Article 5 lists the fundamental rights, but right at the beginning, in a privileged position in relation to the rights provided for in the Constitution, it guarantees basic rights to all. The first is the inviolability of the right to life, which thus takes precedence over everything else. This does not prevent the demarcation of borders from often being difficult to establish. Amendment 45 to the Constitution added a third paragraph, according to which human rights treaties are treated as fundamental rights. This orientation was later extended to ordinary legislation. It expresses a profound respect for the good life. But there are no absolutes in law. Neither is life.
Keywords: right to life; brain death; coma; vegetative state; palliative care; terminal state; consent